Nuclear factor‐kappa B and interleukin‐6 related docetaxel resistance in castration‐resistant prostate cancer1. Issue 5 (4th October 2012) - Codony‐Servat, Jordi; Marín‐Aguilera, Mercedes; Visa, Laura; García‐Albéniz, Xabier; Pineda, Estela; Fernández, Pedro L.; Filella, Xavier; Gascón, Pere; Mellado, Begoña
Abstract BACKGROUND Previous work showed that the NF‐κB survival pathway is activated by docetaxel (D) and contributes to D resistance in prostate cancer. In this study we aimed to investigate the dynamics of the relationship between NF‐κB and IL‐6 in the shift from D‐naive castration‐resistant prostate cancer (CRPC) to D‐resistance in patients and cell lines. METHODS CRPC tumor samples were tested for NF‐κB/p65 and IL‐6 by immunohistochemistry. CRPC patients treated with D were also tested for serum IL‐6 (ELISA). Two D‐resistant cell lines, PC‐3R and DU‐145R, derived from the CRPC cells PC‐3 and DU‐145, respectively, were tested for NF‐κB activation (EMSA), NF‐κB‐related genes expression (RT‐PCR), NF‐κB inhibition (p65 siRNA) and IL‐6 and IL‐8 soluble levels (ELISA). RESULTS In CRPC patients treated with D (n = 72), pre‐treatment IL‐6 level correlated with nuclear NF‐κB/p65 tumor staining and response to D, and was an independent prognostic factor for overall survival. However, IL‐6 level changes under treatment did not correlate with clinical outcome. In PC‐3 and DU‐145 parental CRPC cells, as well as in D‐resistant counterparts, D treatment induced NF‐κB activation. In fact, NF‐κB inhibition was sufficient to re‐sensitize DU‐145R cells to D. Despite enhanced NF‐κB activity, IL‐6 secretion in D‐resistant cell lines was reduced and not induced by D treatment. The same occurred with IL‐8 cytokine. CONCLUSIONS These preclinical and clinical results support a role of NF‐κB and IL‐6 in the resistance to D in CRPC, and support the investigation of targeted therapies to enhance the antitumor activity of D in this patient population. Prostate 73: 512–521, 2013. © 2012 Wiley Periodicals, Inc.